2022
DOI: 10.1002/adom.202201741
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐Device Mass‐Producible Perovskite Photodetector Based on Laser‐Induced Graphene Electrodes

Abstract: because of its unique properties including high light absorption coefficient, high charge carrier mobility, and large charge carrier diffusion length. [11][12][13] Besides, high-quality perovskite films can be fabricated on a large scale by facile and inexpensive solution methods, which promote mass production of perovskite-based optoelectronics devices. [2,14,15] For example, a slot-die printing technology has been recently developed to continuously fabricate a formamidinium cesium lead triiodide (FACsPbI 3 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…LIG has been used as lateral electrodes of the photodetector for signal collection due to its low-cost, scalable, and fast fabrication process, making it a promising material for mass production of optoelectronic devices. [138][139][140][141] In addition, LIG-based lateral electrodes reduce the overall thickness of the photodetectors, leading to decreased strain and increased flexibility for the photodetectors. Qu et al 140 reported a mass-producible optical sensor based on perovskite as a light-sensitive material with LIG contact electrodes.…”
Section: Physical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…LIG has been used as lateral electrodes of the photodetector for signal collection due to its low-cost, scalable, and fast fabrication process, making it a promising material for mass production of optoelectronic devices. [138][139][140][141] In addition, LIG-based lateral electrodes reduce the overall thickness of the photodetectors, leading to decreased strain and increased flexibility for the photodetectors. Qu et al 140 reported a mass-producible optical sensor based on perovskite as a light-sensitive material with LIG contact electrodes.…”
Section: Physical Sensorsmentioning
confidence: 99%
“…[138][139][140][141] In addition, LIG-based lateral electrodes reduce the overall thickness of the photodetectors, leading to decreased strain and increased flexibility for the photodetectors. Qu et al 140 reported a mass-producible optical sensor based on perovskite as a light-sensitive material with LIG contact electrodes. LIG electrodes were derived from polyimide via a photothermal laser manufacturing approach and formamidinium cesium lead triiodide perovskite was spin coated on LIG as a sensing material to make a LIG-perovskite composite with lateral LIG electrodes.…”
Section: Physical Sensorsmentioning
confidence: 99%
“…The manufacturing process (Fig. 4 Bi) of the sensor involved the in-situ synthesis of a laser-induced graphene (LIG) interdigital electrode (IDE) on a flexible PI film using laser direct writing technology [ 65 68 ]. Then, a thin and uniform GO film was drop-casted onto the LIG-IDE to serve as the sensing element.…”
Section: Wearable Sensors For the Measurement Of Plant Phenotypesmentioning
confidence: 99%
“…Conventional impedance sensors are typically rigid because they are constructed using materials like metal or hard plastic, which can potentially cause secondary damage to the fruit (Magar et al, 2021). Fortunately, recent advancements in flexible electronics have led to the extensive research and development of flexible sensors (Huang, Xia, et al, 2023; Qu et al, 2022, 2024), expanding their usability to curved or soft object surfaces and dynamically changing environments (Huang et al, 2024). Therefore, this study aims to develop a flexible impedance non‐destructive grading system that incorporates visual features.…”
Section: Introductionmentioning
confidence: 99%